2021
DOI: 10.3390/app112210612
|View full text |Cite
|
Sign up to set email alerts
|

Renal Acoustic Radiation Force Impulse Elastography in Hypertensive Nephroangiosclerosis Patients

Abstract: Objective: Hypertensive nephroangiosclerosis (HN) represents the second most common cause of chronic kidney disease. Kidney damage secondary to high blood pressure favors the appearance of serum and urinary changes, but also imaging, highlighted by ultrasonography (B-mode, Doppler, Acoustic Radiation Force Impulse Elastography). Acoustic Radiation Force Impulse Elastography (ARFI) represents a new imagistic method which characterizes renal stiffness in the form of shear wave velocity (SWV). Aim: This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The relationship between the level of kidney SWS and renal disease was quite distinct in different studies using VTQ. We found that in some studies, kidney SWS was increased in patients with CKD (5 studies) [19,22,25,34,36], while in others it was decreased (12 studies) [18,23,[27][28][29]31,35,37,38], and four studies showed no relationship between kidney SWS and renal disease [20,32,33,47]. Overall, we found that patients with CKD have a lower kidney SWS than healthy controls with a standardized mean difference of −0.216.…”
Section: Discussionmentioning
confidence: 68%
“…The relationship between the level of kidney SWS and renal disease was quite distinct in different studies using VTQ. We found that in some studies, kidney SWS was increased in patients with CKD (5 studies) [19,22,25,34,36], while in others it was decreased (12 studies) [18,23,[27][28][29]31,35,37,38], and four studies showed no relationship between kidney SWS and renal disease [20,32,33,47]. Overall, we found that patients with CKD have a lower kidney SWS than healthy controls with a standardized mean difference of −0.216.…”
Section: Discussionmentioning
confidence: 68%